2020
DOI: 10.1103/physrevmaterials.4.114405
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected dependence of the anomalous Hall angle on the Hall conductivity in amorphous transition metal thin films

Abstract: Young women in sub-Saharan Africa are disproportionally affected by HIV infection and unintended pregnancies. However, hormonal contraceptive (HC) use may influence HIV risk through changes in genital tract microbiota and inflammatory cytokines. To investigate this, 130 HIV negative adolescent females aged 15-19 years were enrolled into a substudy of UChoose, an open-label randomized crossover study (NCT02404038), comparing acceptability and contraceptive product preference as a proxy for HIV prevention delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 91 publications
1
4
0
Order By: Relevance
“…Indeed, the Berry density shows welldefined functional dependence as a function of energy. Similar effects have been observed in amorphous CoFeB 50 and intrinsic contributions to AHE has been discussed [47][48][49] . This brings up an intriguing possibility -in a structure with a broken symmetry at the interface, an amorphous material should be able to generate spin current and potentially torque a magnet.…”
supporting
confidence: 73%
“…Indeed, the Berry density shows welldefined functional dependence as a function of energy. Similar effects have been observed in amorphous CoFeB 50 and intrinsic contributions to AHE has been discussed [47][48][49] . This brings up an intriguing possibility -in a structure with a broken symmetry at the interface, an amorphous material should be able to generate spin current and potentially torque a magnet.…”
supporting
confidence: 73%
“…[ 17 ] Amorphous samples synthesized under different conditions can present different local atomic structures, although both lack a long‐range structural order. We also note that in amorphous ferromagnetic thin films such as CoFeB obtained by sputtering at room temperature, [ 27,28 ] the conductivity decreases naturally due to disorder, but M and σxyA$\sigma _{xy}^A$ are rather robust against disorder. Unlike previous studies on amorphous magnetic films, our CrGeTe 3 samples irradiated with heavy ions are more significantly affected by amorphization and exhibit totally different transport and magnetic properties from those of the crystalline phase.…”
Section: Discussionmentioning
confidence: 87%
“…Karel et al discussed that increasing transition metal fraction leads the large anomalous Hall angle in amorphous systems. 20 The previous study also proposed introducing a rare-earth element or an element with large SOI to generate a larger nonzero Berry curvature in order to enhance anomalous Hall angle in amorphous systems. In this study, a TM-rich sample showed the large Hall angle tan θ H of about 5%.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Berry curvature effects in amorphous magnetic materials have been discussed recently. [19][20][21] However, since the ANE is not large enough to use in practical application compared with the conventional Seebeck effect, further understanding of the ANE in magnetic materials is necessary to improve thermoelectric efficiency.…”
Section: Introductionmentioning
confidence: 99%